Fault Tolerant Control for Spaceborne Dual Ring Counters with Selective Overriding - Yang, Jung-Min; Jung, Im Y.; Kwak, Seong Woo (Indian journal of science and technology, 2015)
Among primary asynchronous sequential circuits, ring counters are used as an important building block in various spaceborne digital systems. As they are subject to adverse effects of radiation, it is imperative that they be given fault tolerance mechanism for robust operation. This article presents a corrective control scheme for tolerating state transition faults in ring counters. The considered ring counter has the structure of Double Modular Redundancy, in which some selected memory bits of each ring counter module can override the counterpart values of the other module. With this structure, researchers can design a static corrective controller that tolerates any state transition fault occurring to the dual ring counter. Though the state information is unavailable, they can implement a simple fault tolerant control scheme, using corrective control. The proposed control scheme is validated in VHDL experiments.